Features of the Observation Method in Museum Audience Behaviour Research - Jovaišaitė-Blaževičienė, Indrė (Information & Media, 2024)
Audience behaviour research is one of the most relevant topics in the field of museology, as visitor-oriented modern-museology-based museums inevitably need to understand how visitors learn, explore and understand museum information and communication. The article discusses the specifics of the application of observation as one of the oldest scientific research methods in the study of museum audiences. Even though observation is identified as an essential way of studying audience behaviour in real-time, the application of the method still raises questions about the way it is applied, issues of objectivity and the reliability of data. This paper aims to highlight relevant methodological issues in the application of observation and other qualitative methods of museum visitor research in assessing the relationship between the essential research question and the data needed to answer it. A literature review and the results and experiences of the empirical research conducted for the doctoral thesis are used to answer the questions. The empirical study of visitors’ free choice behaviour in the Lithuanian Museum is used to illustrate the relevant features of the monitoring method, while the detailed results of the visitor behaviour monitoring study are presented in a dedicated paper.